Rola pomocy żywnościowej w regionach gospodarczo słabo rozwiniętych - Rutkowska, Irena (Wydział Prawa i Administracji UAM, 1969)
The analysis and the appreciation of the food situation of the world in the post-war period have been carried out on the basis of the statistical data derived from the three consecutive World Food Surveys (of 1946, 1952 and 1963) and from other FAO publications. It has been stated, that in the satisfactory circumstances for the food production (in calories) in the world scale, its unequal distribution among different economic regions occurs, what means the disadvantage for the underdeveloped regions in calory consumption and in animal's protein consumption. Owing to the limited possibilities in increasing internal food production and in the commercial food import, the improving of diet in underdeveloped regions can be achieved by means of foreign assistance food supplies. The analysis of food aid in the post-war period leads to the conclusions, that the scope of the food aid doesn't result in the improving of diet in the most deficit countries. The conditions of this aid, based on bilateral agreements, are convenient for the donor countries, but not suitable for the recipient countries. So there is an urgent need for increasing the food aid programs on the base of multilateral agreements in a larger scale.
The Role of Food Assistance in Underdeveloped Regions